130 Skull Base Chordomas in Children and Young Adults. (August 2016) - Hulou, M. Maher; Rassi, Marcio S.; Almefty, Kaith; Bi, Wenya Linda; Dunn, Ian F.; Smith, Timothy R.; Al-Mefty, Ossama
Abstract : INTRODUCTION: Skull base chordomas are rare tumors, with less than 5% occurring in patients younger than 20 years of age. Current understanding and a consensus management strategy for pediatric chordomas remain lacking. We investigated the clinical and radiological features of chordomas in young patients, with an emphasis on surgical outcomes and predictors of survival following our management protocol of radical surgical resection with adjuvant high-dose radiotherapy. METHODS: Data from 31 patients, age 22 years or younger, referred to the senior author (OAM) from 1993 to 2008 were reviewed. Thirteen patients that had received previous treatment did not require surgical intervention at referral. Eighteen patients were treated in accordance with our protocol and included in the survival analysis, with mean follow-up of 123 months (range 12-263 months). Age, sex, extent of resection, previous treatments, number of surgeries for tumor removal, and histopathology were analyzed, with correlation to progression-free survival. RESULTS: Mean age of diagnosis among the cohort (17 girls, 14 boys) was 10.6 years. Abducens nerve palsy was the most common presenting symptom. Radiological features mirrored those observed in adults; however, pediatric chordomas were frequently large at presentation with involvement of multiple anatomical compartments. Increased progression-free survival was associated with gross total resection (mean 192 months), compared with subtotal resection (mean 25.6 months; P = .025); typical histopathology (mean 174.9 months), compared with atypical pathology (mean 17.3 months; P = .019), and primary status at time of surgery (mean 195 months), compared with surgery on residual or progressive tumors (mean 27.8 months; P = .016). CONCLUSION: Long-term disease-free survival in children harboring skull base chordomas can be achieved by radical surgical resection followed by high-dose proton/photon radiation therapy, especially on initial diagnosis of the tumor.